THE THEOLOGICAL VIEW OF THEODORE SKUMYNOVYCH ON THE REASONS OF DECAY OF THE ORTHODOX EAST IN THE WORK "PRZYCZYNY PORZUCENIA DISUNIEY PRZEZACNEMU NARODOWI RUSKIEMU PODANE" (1643) - Ткачук, Руслан (Taras Shevchenko National University of Kyiv (Ukraine), 2022)
In the article it is researched the polemical work of former Father Superior of St. Michael cloister in Kyiv Theodore Skumynovych "Przyczyny porzucenia Disuniey przezacnemu narodowi ruskiemu podane" (1643); it is disclosed the view of the writer on the reasons of decay of the orthodox East, stated the used stylistic devices in book. In his work Theodore Skumynovych substantiated his thought that separation of the East church from Rome caused the decay of the countries, in which one took up the principal positions. Idealizing the age of unity of church, the writer contrastingly opposed the glorious Christian past of Syria and it's tragic present. Criticizing the Greek clergy for rejection to dialog of consolidation with Rome, the polemicist narrated about the horrible tragedy of Catholics, which happened in Constantinople in 1182 year. Theodore Skumynovych turned his eyes also on church's life of Egypt, Libya, Numidia, Germany, France, Hungary, Italy. The writer rated Ukraine to the same category of countries as England, Denmark, Sweden, to which Lord revealed His mercy and long suffering, because believed in their conversion to Catholicism. Explaining the reasons of spiritual regress of the countries of the Eastern Church, the polemicist concerned the tragic milestone of history of Ancient Rus. As the decay of Byzantine empire, the author analyzed the military and political troubles of Rus in the context of catholic conception of history, in which prosperity of the nations depended on the obedience to the authority of Pope. The flourishing of Ancient Rus, which took place at the times of the Kyiv prince Volodymyr and Yaroslav the wise, Theodore Skumynovych attributed with following of the Kyiv metropolitanate the lead of the Church of Rome. On the contrary, the spread of Michael Cerularius's schism in Rus provoked God's anger, which exhibited in fratricidal war, the occupation of its land by the Golden Horde and the Duchy of Lithuania.

Досліджено полемічний твір письменника-католика, екс-ігумена Михайлівського монастиря в Києві Теодора Скуминовича "Przyczyny porzucenia Disuniey przezacnemu narodowi ruskiemu podane" (1643); розкрито погляд книжника на причини занепаду православного Сходу, вказано застосовані стилістичні прийоми текстотворення. У своєму творі Теодор Скуминович обґрунтував думку про те, що відокремлення Східної церкви від Рима спричинило занепад держав, у яких вона займала провідні позиції. Ідеалізуючи добу єдності церкви, письменник контрастно протиставив величне християнське минуле Сирії її трагічній сучасності. Критикуючи грецьке духовенство за відмову вести об'єднавчий діалог із Римом, Теодор Скуминович розповів про жахливу трагедію католиків, що сталася в царському місті у 1182 р. Свій погляд письменник також спрямував на церковне життя Єгипту, Лівії, Нумідії, Німеччини, Франції, Угорщини, Італії. Книжник зараховував Україну до тієї самої категорії країн, що й Англію, Данію та Швецію, яким Бог явив Своє милосердя і довготерпіння. Пояснюючи причини духовного регресу держав східнохристиянської ойкумени, Теодор Скуминович не оминув трагічні віхи історії Стародавньої Русі. Як і занепад Візантійської імперії, полеміст розглядав військові та внутрішньополітичні негаразди "Руської монархії" в контексті католицької концепції історії, у якій добробут народів залежав від послуху владі Папи Римського. Розквіт Давньоруської держави, що припав на роки князювання Володимира-Хрестителя та Ярослава Мудрого, письменник пов'язував з дотриманням Київською митрополією римоцентричної еклезіології. Натомість поширення на Руській землі схизми Михаїла I Керуларія викликало Божий гнів, що виявився у міжусобницьких чварах, братовбивчій війні, її загарбанні військами Золотої Орди та Великого князівства Литовського.
БОГОСЛОВСЬКИЙ ПОГЛЯД ТЕОДОРА СКУМИНОВИЧА НА ПРИЧИНИ ЗАНЕПАДУ ПРАВОСЛАВНОГО СХОДУ У ТВОРІ "PRZYCZYNY PORZUCENIA DISUNIEY PRZEZACNEMU NARODOWI RUSKIEMU PODANE" (1643)
Keywords: Theodore Skumynovych; Ukrainian polemical literature; orthodox; Catholicism; Protestantism; Union of Brest (1596); Patriarchate of Constantinople; Byzantine empire; Теодор Скуминович; українська полемічна література; православ'я; католицизм; протестантизм; Берестейська унія; Константинопольська церква; Візантія